Low-complexity massive MIMO channel estimation for mmWave systems via matrix completion - Jiafeng QIU (Dianxin kexue)
Due to the high computational complexity of mmWave massive MIMO systems realizing reliable channel estimation,a low-complexity mmWave beamspace channel estimation algorithm was proposed utilizing the inherent low-rank of the mmWave channel.The proposed algorithm jointly exploited the channel sparsity in the beamspace domain and its low-rank property in the antenna domain to provide more accurate recovery,especially for shorter training intervals.By regarding the channel estimation as matrix completion problem,the proposed algorithm was based on the alternating direction method of multipliers with fast convergence properties and exploited fast randomized singular value thresholding to significantly reduce the corresponding complexity.The simulation result shows that the proposed algorithm can achieve satisfactory channel estimation performance while maintaining low complexity.